PENGARUH SPIRITUALITAS TERHADAP SERVANT LEADERSHIP DAN KINERJA PIMPINAN - Sudirman, Subhan Ajrin (Universitas Islam Negeri Imam Bonjol Padang, 2017)
Within the scope of the organization, a number of studies have revealed the positive impact of spirituality for the organization. As many experts point out that spirituality in the workplace benefits organizations at least at two levels, organizational levels and individual levels. The influence of spirituality on the organizational level can be related to work attitude of employees, leadership, culture and organizational performance. At the individual level, spirituality can positively affect the physical, mental and personal effectiveness of the individual. Numerous studies have shown that organizations that pay attention to spirituality have an effect on performance improvement. The issue of spirituality and the scope of the individual is related to the need of the individual in obtaining the meaning, the most important meaning, or the deepest meaning and tranquility in his life and the needs of the environment that can support his own potential growth. Environmental circumstances, both micro environments, such as workplaces and the national and global community environments referred to as full of competitive circumstances have put great pressure on and push the need for spirituality to manage themselves through mechanisms that give meaning and awareness of the purpose of life.